2018
DOI: 10.1021/acs.orglett.8b03520
|View full text |Cite
|
Sign up to set email alerts
|

β-Chloroaldehydes from Trapping Zirconium Enolates Produced in Asymmetric 1,4-Additions

Abstract: Zirconium enolates, derived from copper-catalyzed asymmetric conjugate additions, are trapped with the Vilsmeier–Haack reagent. Asymmetric additions generate quaternary carbon centers with high enantioselectivity (generally ∼90% ee), and the enolates are converted to unsaturated β-chloroaldehydes (41–57% yields). The reaction tolerates changes to the nucleophile, can be used to form five-, six-, or seven-membered ring products, and is scalable to 5 mmol, and the products are readily elaborated by condensation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Having demonstrated that 9 could reliably be added to 6 , we next turned our attention to the preparation of a suitable intermediate for the synthesis of the desired product. The trapping of zirconium enolates is a challenging problem, and we recently reported trapping reactions using the Vilsmeier–Haack reagent to give β-chloroaldehydes from our ACA zirconium enolates . It was found that this trapping protocol also worked for our substrate; using 16.5 mmol of 6 , 3.6 g of 11 (corresponding to 69% yield) could be obtained with 92% ee, requiring minimal modification (Scheme , steps a and b).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Having demonstrated that 9 could reliably be added to 6 , we next turned our attention to the preparation of a suitable intermediate for the synthesis of the desired product. The trapping of zirconium enolates is a challenging problem, and we recently reported trapping reactions using the Vilsmeier–Haack reagent to give β-chloroaldehydes from our ACA zirconium enolates . It was found that this trapping protocol also worked for our substrate; using 16.5 mmol of 6 , 3.6 g of 11 (corresponding to 69% yield) could be obtained with 92% ee, requiring minimal modification (Scheme , steps a and b).…”
mentioning
confidence: 88%
“…The trapping of zirconium enolates is a challenging problem, 14 and we recently reported trapping reactions using the Vilsmeier− Haack reagent to give β-chloroaldehydes from our ACA zirconium enolates. 15 It was found that this trapping protocol also worked for our substrate; using 16.5 mmol of 6, 3.6 g of 11 (corresponding to 69% yield) could be obtained with 92% ee, requiring minimal modification (Scheme 3, steps a and b). (See the Supporting Information for optimization.…”
mentioning
confidence: 99%
“…Organozirconium compounds are another class of organometallic reagents that have been used widely in the synthesis of complex molecules. Recently, Fletcher and co-workers demonstrated the applicability of a hydrozirconation in the ACA reaction to non-heterocyclic conjugated substrates [22][23][24][25][26], while the Šebesta group was the first to report the copper-catalysed addition of organozirconium reagents to N-substituted 2,3dehydro-4-piperidones (Scheme 4A) [27]. In the latter work, the organozirconium reagents were generated first in situ by the hydrozirconation of alkenes.…”
Section: Review Copper-catalysed C-c Bond-forming Reactions At the Hementioning
confidence: 99%
“…Products 46 were obtained in high enantiopurities of up to 98% and were additionally prone to further functionalization. 66 This reaction was recently employed in the total synthesis of taxol core derivative 47 (Scheme 13). 67 This work improved on Baran's elegant synthesis of taxadienone, 68 which utilized the ACA of Me 3 Al using Alexakis's protocol.…”
Section: Scheme 12 the First Zr-enolate Trapping Reactions Initiated mentioning
confidence: 99%